Very Intense Distinct Blue and Red Photoluminescence Emission in MgTiO 3 Thin Films Prepared by the Polymeric Precursor Method: An Experimental and Theoretical Approach - Ferri, ElÍdia Aparecida Vetter; Mazzo, Tatiana Martelli; Longo, Valeria Moraes [UNESP]; Moraes, Eduardo; Pizani, Paulo SÉrgio; Li, MÁximo Siu; Espinosa, JosÉ Waldo MartÍnez; Varela, José Arana [UNESP]; Silva, Elson Longo da [UNESP] (American Chemical Society (ACS), 2012)
MgTiO3 (MTO) thin films were prepared by the polymeric precursor method with posterior spin-coating deposition. The films were deposited on Pt(111)/Ti/SiO2/Si(100) substrates and heat treated at 350 °C for 2 h and then heat treated at 400, 450, 500, 550, 600, 650 and 700 °C for 2 h. The degree of structural order−disorder, optical properties, and morphology of the MTO thin films were investigated by X-ray diffraction (XRD), micro-Raman spectroscopy (MR), ultraviolet− visible (UV−vis) absorption spectroscopy, photoluminescence (PL) measurements, and field-emission gun scanning electron microscopy (FEG-SEM) to investigate the morphology. XRD revealed that an increase in the annealing temperature resulted in a structural organization of MTO thin films. First-principles quantum mechanical calculations based on density functional theory (B3LYP level) were employed to study the electronic structure of ordered and disordered asymmetric models. The electronic properties were analyzed, and the relevance of the present theoretical and experimental results was discussed in the light of PL behavior. The presence of localized electronic levels and a charge gradient in the band gap due to a break in the symmetry are responsible for the PL in disordered MTO lattice.